Microemulsion-based novel transdermal delivery system of tetramethylpyrazine: preparation and evaluation in vitro and in vivo - Zhao JH (Dove Medical Press, 2011)
Ji-Hui Zhao, Li Ji, Hui Wang, Zhi-Qiang Chen, Yong-Tai Zhang, Ying Liu, Nian-Ping FengSchool of Pharmacy, Shanghai University of Traditional Chinese Medicine, Shanghai, People's Republic of ChinaObjective: To deliver 2,3,5,6-tetramethylpyrazine (TMP) in a relatively large dose through a transdermal route and facilitate the practical application of microemulison in transdermal drug delivery.Methods: The pseudo-ternary phase diagram for microemulsion regions was constructed using isopropyl myristate as oil phase, Labrasol® as surfactant, and Plurol® Oleique CC 497 as cosurfactant. A uniform experimental design was applied for formulation optimization. In vitro skin permeation experiments of six formulations were undertaken with TMP transdermal patch (EUDRAGIT® E100 as matrix) and TMP saturated solution as controls. We prepared TMP-oil dispersed in water-ethylene vinyl acetate-transdermal therapeutic system (TMP-O/W-EVA-TTS) with microemulsion as reservoir and EVA membrane as release liner; pharmacokinetic and brain distribution studies in rats were conducted with TMP transdermal patches as control.Results: The skin fluxes of TMP from microemulsions were 8.2- to 26.7-fold and 0.9- to 4.7-fold higher than those of TMP transdermal patch and TMP saturated solution, respectively, and were strongly affected by the microemulsion composition. The improvement in TMP solubility as well as the skin permeation enhancement effect of microemulsion components contributed mainly to transdermal delivery facilitation. In the pharmacokinetic study, the relative bioavailability of TMP-O/W-EVA-TTS was 350.89% compared with the TMP transdermal patch. Higher and more stable TMP contents in rat plasma were obtained after administration of TMP-O/W-EVA-TTS than after application of TMP transdermal patch. In the brain distribution study, higher rate and extent of TMP distribution to brain, and lower rate of TMP clearance from brain were observed after transdermal administration of TMP-O/W-EVA-TTS than after application of TMP transdermal patch.Conclusion: The novel transdermal delivery system prepared in this study showed a remarkable skin permeation improvement of microemulsion and facilitated its practical application in transdermal drug delivery. With this system as a vehicle, a relatively large dose of TMP could enable successful drug delivery via the transdermal route.Keywords: TMP, microemulsion, EVA membrane, transdermal delivery, pharmacokinetics, brain distribution